Leuprolide Acetate Treatment for Ovarian Cysts in Breast Cancer Patients Under Tamoxifen Therapy - Şafak Yılmaz Baran; Gulsen Dogan Durdag; Songul Alemdaroglu; Sirin Aydin; Husnu Celik (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of this study is to evaluate the outcomes of gonadotropin-releasing hormone agonist treatment for ovarian cysts, which are developed during tamoxifen use due to breast cancer.